2017
DOI: 10.1016/j.jconrel.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-functionalized polymer graft surface eluting MK2 inhibitory peptide to improve hemocompatibility and anti-neointimal activity

Abstract: The leading cause of synthetic graft failure includes thrombotic occlusion and intimal hyperplasia at the site of vascular anastomosis. Herein, we report a co- immobilization strategy of heparin and potent anti-neointimal drug (Mitogen Activated Protein Kinase II inhibitory peptide; MK2i) by using a tyrosinase-catalyzed oxidative reaction for preventing thrombotic occlusion and neointimal formation of synthetic vascular grafts. The binding of heparin–tyramine polymer (HT) onto the polycarprolactone (PCL) surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…JCI Insight 2021;6(19):e142339 https://doi.org/10.1172/jci.insight.142339 of particular importance in the vascular graft treatment setting used herein, in which a single prophylactic treatment was given intraoperatively to provide a therapeutic benefit throughout the graft healing process. Increased cellular uptake and retention make MK2i-NPs the ideal treatment strategy over previously explored methods, such as a heparin-functionalized graft that elutes free MK2i peptide over time (58), which does not have the intracellular bioavailability benefits that come with PPAA complexation. A previous vascular graft study showed the greatest VSMC proliferation and inflammation in the first week after surgery, which waned thereafter (47), highlighting a critical window through which intraoperative vascular treatments must be retained as the vascular graft heals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JCI Insight 2021;6(19):e142339 https://doi.org/10.1172/jci.insight.142339 of particular importance in the vascular graft treatment setting used herein, in which a single prophylactic treatment was given intraoperatively to provide a therapeutic benefit throughout the graft healing process. Increased cellular uptake and retention make MK2i-NPs the ideal treatment strategy over previously explored methods, such as a heparin-functionalized graft that elutes free MK2i peptide over time (58), which does not have the intracellular bioavailability benefits that come with PPAA complexation. A previous vascular graft study showed the greatest VSMC proliferation and inflammation in the first week after surgery, which waned thereafter (47), highlighting a critical window through which intraoperative vascular treatments must be retained as the vascular graft heals.…”
Section: Discussionmentioning
confidence: 99%
“…MK2i-NPs are a flexible and potent alternative to drug-eluting stents or balloons for delivery of compounds targeting IH. One important study described surface-based delivery of peptide from a synthetic polymer film that could potentially be developed as a vascular graft material ( 58 ). This biomaterial was functionalized with anionic heparin to which the cationic MK2i peptide was electrostatically adhered, allowing slow release of free MK2i peptide from the surface when applied in cultures.…”
Section: Discussionmentioning
confidence: 99%
“…First, heparin, a universal anticoagulant, was immobilized on graft surfaces to reinforce the antithrombotic properties. [ 30–41 ] Heparin interacted with antithrombin III and enhanced inhibition of blood coagulant factors including factor Xa and thrombin, thereby avoiding blood coagulation. [ 42 ] Heparin in multiple layers can be immobilized on ε ‐polycaprolactone (PCL) graft surfaces by combining EDC/NHS coupling and layer‐by‐layer assembly, preventing long‐term thrombus formation.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%
“…Graft stenosis and occlusion are a result of neointimal hyperplasia that is caused by smooth muscle cells (SMCs). Even though SMCs are necessary for the structure and the function of the neovessel, its abnormal proliferation can damage the vascular graft [ 102 , 103 ]. Transforming growth factor-beta (TGF-β) and platelet-derived growth factor (PDGF) have shown their ability to suppress the pathway of SMCs in neointimal hyperplasia [ 103 ].…”
Section: Nanostructured Film Surfacesmentioning
confidence: 99%